2019
DOI: 10.1200/jco.18.00822
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Children With Hypodiploid Acute Lymphoblastic Leukemia: A Retrospective Multinational Study

Abstract: PURPOSE We determined the prognostic factors and utility of allogeneic hematopoietic cell transplantation among children with newly diagnosed hypodiploid acute lymphoblastic leukemia (ALL) treated in contemporary clinical trials. PATIENTS AND METHODS This retrospective study collected data on 306 patients with hypodiploid ALL who were enrolled in the protocols of 16 cooperative study groups or institutions between 1997 and 2013. The clinical and biologic characteristics, early therapeutic responses as determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
98
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 30 publications
5
98
0
1
Order By: Relevance
“…Nevertheless, these data suggest that treatment intensification including allogeneic HSCT is not sufficient for these patients. In addition, both the Children's Oncology Group and the Ponte di Legno Childhood ALL working Group reported that HSCT did not improve outcome for patients with hypodiploid ALL . Therefore, we should consider other strategies for these patients, including new drugs such as blinatumomab, or even chimeric antigen receptor T‐cell therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, these data suggest that treatment intensification including allogeneic HSCT is not sufficient for these patients. In addition, both the Children's Oncology Group and the Ponte di Legno Childhood ALL working Group reported that HSCT did not improve outcome for patients with hypodiploid ALL . Therefore, we should consider other strategies for these patients, including new drugs such as blinatumomab, or even chimeric antigen receptor T‐cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…reported that MRD is an important prognostic indicator for childhood hypodiploid ALL . Recently, the Ponte di Legno Childhood ALL Working Group reported an international retrospective study in which the outcomes were significantly better in MRD‐stratified protocols than in MRD‐non‐stratified protocols . EFS of hypodiploid patients who were MRD negative at the end of induction was >70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the study group is small because of the rarity of the entity studied, it is one of the largest such groups in the literature to date. Their results suggest that young adults (<30 years of age) with lowhypodiploid B-ALL achieving MRD levels of <0Á1% at the end of induction therapy have an acceptable outcome with intensive chemotherapy alone, as others have reported for children Mullighan et al, 2015;Pui et al, 2019). However, patients older than 35 years of age had a very poor prognosis for relapse and survival despite achieving an acceptable MRD response to induction therapy.…”
mentioning
confidence: 81%
“…141 In the latter group, it should be noted that some studies have examined the role of HSCT in pediatric patients with hypodiploid B-ALL, and it is unclear whether HSCT improves outcomes when given in CR1 in patients who are MRD-positive at the EOI. [152][153][154][155] However, HSCT for hypodiploid ALL may be considered in the context of a clinical trial.…”
Section: Hematopoietic Stem Cell Transplantmentioning
confidence: 99%